Costs of reducing phosphorus runoff from horse pastures in Sweden - Möller, Annie (SLU/Dept. of Economics, 2020)
Eutrophication is an environmental issue that causes deterioration of inland waters and oceans. It is induced by leaching of nutrients from different sources. One such source that has been getting attention lately is the leaching of nutrients from horse pastures. This thesis investigates if reducing the number of horses and mucking pastures is a cost-efficient measure to reduce the leaching of phosphorus. A minimization model was developed where the costs of reducing horses and removing dung were minimized for different levels of reduction of phosphorus runoff. The costs of reducing horses were estimated as the loss in consumer surplus, and the cost of removing manure was calculated based on the cost of labor. The results indicate that the measure is not cost-effective, with a marginal cost at 281 559 710 SEK and a total cost at 259 034 933 SEK for a reduction level at 10% of the leaching caused by the horses. Compared with other studies the marginal cost was significantly larger, hence the conclusion is that the measure cannot be considered cost-efficient.